The The Influence Of Supply Chain Management (SCM) and Innovation Strategy On Company Performance - Muhammad Afif Maulana (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
In this study using a quantitative approach using primary data. The purpose of this study is to test and determine the influence of Supply Chain Management and Company Innovation Strategy on Company Performance. Data was taken through questionnaires distributed to respondents of the H.I Family Branch, the sample used a saturated sample of 30 respondents. The data analysis method used is multiple linear regression analysis which has previously met the requirements of the classical assumption test and has also been tested hypothesically using t and f tests and R2 tests. Data processing is carried out using the SPSS application. In Test t Supply Chain Management (SCM) (X1) has a positive effect on Company Performance (Y) significantly and T test obtained Innovation Strategy (X2) has a significant positive effect on Company Performance (Y).